La Tradición Sofista en Paulo Freire - da Silva, Tatiane; da Cunha, Marcus Vinicius (Pontificia Universidad Católica del Perú, 2023)
This article aims to demonstrate that the philosophical and educational conceptions of the Brazilian scholar Paulo Freire are rooted in a discursive tradition with origins dating back to the inception of philosophy. This tradition, known as rhetoric, originated with the sophists of Classical Greece, giving rise to an educational approach focused on the holistic development of the individual’s creative, affective, communicative, ethical, and political capacities, all aimed at the betterment of the common good. The first section of the article introduces the theoretical underpinnings and techniques that constitute this pedagogical framework. The subsequent section examines Freire’s philosophical and educational concepts within the context of Sophistic principles.

Este artículo busca mostrar que las concepciones filosóficas y educativas del pensador brasileño Paulo Freire pertenecen a una tradición discursiva cuyo origen se remonta a los inicios de la filosofía. Esta tradición llamada retórica se inició con los sofistas que trabajaron en la Grecia clásica y dio origen a una pedagogía cuyo fin es la formación plena del individuo para actuar en sociedad a través de su potencial creativo, afectivo, comunicativo, ético y político, orientado al bien común. La primera parte del artículo presenta los fundamentos teóricos y técnicas que componen esta propuesta pedagógica. La segunda parte discute los conceptos filosóficos y educativos de Freire a la luz de los conceptos sofistas.

Este artigo procura mostrar que as concepções filosóficas e educacionais do pensador brasileiro Paulo Freire pertencem a uma tradição discursiva cuja origem remonta aos primórdios da filosofia. Essa tradição denominada retórica teve início com os sofistas que atuaram na Grécia Clássica e deu origem a uma pedagogia cujo propósito é a formação plena do indivíduo para atuar na sociedade por meio de seu potencial criativo, afetivo, comunicativo, ético e político, visando ao bem comum. A primeira parte do artigo apresenta os fundamentos teóricos e as técnicas que compõem essa proposta pedagógica. A segunda parte discute as concepções filosóficas e educacionais freireanas à luz dos conceitos da Sofística.
The Sophist Tradition in Paulo Freire
A Tradição Sofista em Paulo Freire
Keywords: Paulo Freire; Rhetoric; Sophistic; Pedagogical Theories; Paulo Freire; Retórica; Sofística; Teorías Pedagógicas; Paulo Freire; Retórica; Sofística; Teorias Pedagógicas; https://purl.org/pe-repo/ocde/ford#5.03.00